A UK general practice population cohort study investigating the association between lipid lowering drugs and 30-day mortality following medically attended acute respiratory illness - Joshi, Roshni; Venkatesan, Sudhir; Myles, Puja R. (PeerJ, 2016)
Background: Cholesterol lowering drugs HMG-CoA reductase inhibitors (statins) and PPARα activators (fibrates) have been shown to reduce host inflammation via non-disease specific immunomodulatory mechanisms. Recent studies suggest that commonly prescribed drugs in general practice, statins and fibrates, may be beneficial in influenza-like illness related mortality. This retrospective cohort study examines the association between two lipid lowering drugs, statins and fibrates, and all-cause 30-day mortality following a medically attended acute respiratory illness (MAARI). Methods: Primary care patient data were retrospectively extracted from the UK Clinical Practice Research Datalink (CPRD) database. The sample comprised 201,179 adults aged 30 years or older experiencing a MAARI episode. Patient exposure to statins or fibrates was coded as separate dichotomous variables and deemed current if the most recent GP prescription was issued in the 30 days prior to MAARI diagnosis. Multivariable logistic regression and Cox regression were used for analyses. Adjustment was carried out for chronic lung disease, heart failure, metformin and glitazones, comorbidity burden, socio-demographic and lifestyle variables such as smoking status and body mass index (BMI). Statistical interaction tests were carried out to check for effect modification by gender, body mass index, smoking status and comorbidity. Results: A total of 1,096 (5%) patients died within the 30-day follow up period. Of this group, 213 (19.4%) were statin users and 4 (0.4%) were fibrate users. After adjustment, a significant 35% reduction in odds [adj OR; 0.65 (95% CI [0.52–0.80])] and a 33% reduction in the hazard [adj HR: 0.67 (95% CI [0.55–0.83])] of all-cause 30-day mortality following MAARI was observed in statin users. A significant effect modification by comorbidity burden was observed for the association between statin use and MAARI-related mortality. Fibrate use was associated with a non-significant reduction in 30-day MAARI-related mortality. Conclusion: This study suggests that statin use may be associated with a reduction in 30-day mortality following acute respiratory illness that is severe enough to merit medical consultation. Findings from this study support and strengthen similar observational research while providing a strong rationale for a randomised controlled trial investigating the potential role of statins in acute respiratory infections.